The Relation Between Helicobacter Pylori Infection and Symptoms of COVID-19 - Warkaa Mohammed Khadim; Alaa Ali Matrood; Khairi Jameel Al-Ruaby (Genius Journals, 2022)
Helicobacter pylori (H. pylori) represent one of the most prevalent pathogens in humans, which affecting more than half of the population. Infected people usually remain a symptomatic, but, approximately 30% of individuals may develop gastro-duodenal disease with symptoms. In COVID -19 patients, the most prevalent GI symptoms include nausea, vomiting, abdominal pain and diarrhea, which can occur in up to 50% of the patients ,Due to the presence of H. pylori, which is directly linked to the progression of the infection
Keywords: Helicobacte; gastrointestinal symptoms; COVID-19